Regulation of lung oxidative damage by endogenous superoxide dismutase in sepsis - Constantino, Larissa (Intensive Care Med Exp, 2014)
BACKGROUND: The purpose of this research is to study the relationship between superoxide dismutase (SOD) and lung redox state in an animal model of sepsis. METHODS: Sepsis was induced in rats by the cecal ligation and perforation model (CLP). After 3, 6, and 12 h, CLP protein content and expression of SOD1, SOD2, and SOD3 were evaluated, and SOD activity was assessed. Oxidative damage was determined by quantifying nitrotyrosine content. Lung localization of SOD3 was performed by immunohistochemistry. The protective effect of a SOD mimetic on oxidative damage, inflammation, and lung permeability was assessed 12 and 24 h after sepsis induction. RESULTS: Lung levels of SOD1 decreased 3 and 12 h after sepsis, but SOD2 and SOD3 increased, as well as SOD activity. These alterations were not associated with changes in sod gene expression. Nitrotyrosine levels increased 3 and 12 h after sepsis. The administration of a SOD mimetic decreased nitrotyrosine and proinflammatory cytokine levels and improved lung permeability. CONCLUSIONS: SOD2 and SOD3 increased after sepsis induction, but this was insufficient to protect the lung. Treatments based on SOD mimetics could have a role in lung injury associated with sepsis.